Elevated levels of a disintegrin and metalloproteinase 8 in gingival crevicular fluid of patients with periodontal diseases - Sakornrat Khongkhunthian (2018)
Background: A disintegrin and metalloproteinase 8 (ADAM8) is involved in inflammation and is essential for osteoclastogenesis. Elevated ADAM8 levels are detected in human serum and other body fluids in several inflammatory conditions. Therefore, we hypothesized that ADAM8 levels are also raised in gingival crevicular fluid (GCF) of patients with periodontal diseases. Methods: Forty-five patients with periodontal diseases (n = 15 for each group: the group of patients with gingivitis, the group with aggressive periodontitis [AgP], and the group with chronic periodontitis [CP]) and 15 volunteers who exhibited healthy gingiva were recruited. Four periodontal parameters, gingival index, plaque index, probing depth, and clinical attachment level, were recorded before GCF collection. The presence of ADAM8 in GCF was shown by immunoblotting using anti-human ADAM8 polyclonal antibody against its prodomain, and the ADAM8 levels were measured by an enzyme-linked immunosorbent assay. Results: Four immunoreactive bands at 120, 70, 50, and <30 kDa were detected in the groups of patients with periodontitis, whose intensities were stronger than those in the group of patients with gingivitis, consistent with significantly greater ADAM8 levels in both groups of patients, with either CP or AgP, than those in the group of patients with gingivitis and in the group that was healthy (P <0.001). Moreover, the ADAM8 levels correlated significantly with the four periodontal parameters (P <0.001), indicating that ADAM8 levels are positively associated with the degree of periodontal tissue inflammation and destruction. Conclusions: The ADAM8 levels are elevated in the GCF of patients with periodontal diseases, including gingivitis, CP, and AgP, in comparison to control participants who are healthy, and they correlate with four clinical parameters that reflect the degree of disease severity.